Interaction between small pelagic purse seine fishery and its top predators : case study in the eastern Adriatic Sea - Zorica, Barbara (Array, 2018)
Due to very good collaboration with one commercial purse seiner, using “Srdelara” and operating in fishing zone G, preliminary data concerning the interaction between small pelagic purse seine fishery and its predators were obtained. According to the notes taken by experience observer on-board in period from year 2013 to 2016, seems that tunas, dolphins and swordfish were the faithful companions of purse seiner fisherman with abundance of 68.6%, 22.0% and 9.4%, respectively. Although they were present all year round, their monthly pattern of appearance indicated that less tunas were recorded in May-June, more dolphins were noted from July to October while swordfish were mostly abundant in winter (January-March). Within the investigated period, slightly increasing trend of tuna and dolphins’ appearance was recorded, although statistically not significant. Analysing possible correlation between purse seine catches and predator’s abundances, revealed that appearance of tuna had negative impact on the catches (dispersion of schools), while realised catches in presence of dolphins were quite good so it seems that they tend to round up small pelagic fish schools.